Mesenchymal and trophoblast immunophenotype of multipotent stromal cells from human placenta - Shablii, V.A.; Kuchma, M.D.; Kyryk, V.M.; Svitina, H.M.; Shablii, Yu.M.; Lukash, L.L.; Lobintseva, G.S. (Вiopolymers and Cell, 2014)
The investigation of trophoblast markers expression in the mesenchymal stromal cells of placental tissue before and after their isolation and cultivation. Methods. Placental multipotent mesenchymal stromal cells (MMSC) were obtained by culturing the adhesive fraction of cells enzymatically isolated from the placental tissue. The placental derived cells were immunophenotyped by flow cytometry and immunocytochemistry. Results. It was shown that the placental MMSC express the trophoblast markers: human chorionic gonadotropin, pan-cytokeratin, epidermal growth factor receptor HER2. MMSC-like populations of CD90⁺CD73⁺CD45⁻CD34–⁻CD14⁻-cells and CD90⁻CD73⁺CD45⁻CD34⁻CD14⁻-cells are presented in the placental tissue. Conclusions. The placental MMSC simultaneously express mesenchymal and trophoblast markers. Мета. Дослідити експресію маркерів трофобласта в мультипотентних стромальних клітинах у тканині плаценти та за умов їхнього культивування. Методи. Мультипотентні мезенхімальні стромальні клітини (ММСК) отримували культивуванням адгезивної фракції суспензії клітин тканини плаценти, імунофенотипування клітин проводили за допомогою проточної цитофлуорометрії та імуноцитохімії. Результати. Показано, що ММСК плаценти експресують маркери трофобласта: хоріонічний гонадотропін, цитокератини АЕ1/АЕ3, рецептор епідермального фактора росту HER2. У тканині плаценти присутні подібні за імунофенотипом до ММСК популяції CD90⁺CD73⁺CD45⁻CD34–⁻CD14⁻- клітин і CD90⁺CD73⁺CD45⁻CD34–⁻CD14⁻-клітин. Висновки. Плацентарні ММСК одночасно експресують мезенхімальні та трофобластні маркери. Цель. Исследовать экспрессию маркеров трофобласта в мультипотентных стромальных клетках в ткани плаценты и в условиях их культивирования. Методы. Мультипотентные мезенхимальные стромальные клетки (ММСК) получали культивированием адгезивной фракции суспензии клеток ткани плаценты, иммунофенотипирование клеток проводили с помощью проточной цито- флуорометрии и иммуноцитохимии. Результаты. Показано, что ММСК плаценты экспрессируют маркеры трофобласта: хорионический гонадотропин, цитокератины АЕ1/АЕ3, рецептор эпидермального фактора роста HER2. В ткани плаценты присутствуют похожие по иммунофенотипу на ММСК популяции CD90⁺CD73⁺CD45⁻CD34–⁻CD14⁻-клеток и CD90⁺CD73⁺CD45⁻CD34–⁻CD14⁻-клеток. Выводы. Плацентарные ММСК одновременно экспрессируют мезенхимальные и трофобластные маркеры.